Immediate, short‐, and long‐term changes in tracheal stent diameter, length, and positioning after placement in dogs with tracheal collapse syndrome. (20th February 2018) - Raske, Matthew; Weisse, Chick; Berent, Allyson C.; McDougall, Renee; Lamb, Kenneth
Abstract : Background: Intraluminal tracheal stenting is a minimally invasive procedure shown to have variable degrees of success in managing clinical signs associated with tracheal collapse syndrome (CTCS) in dogs. Objectives: Identify immediate post‐stent changes in tracheal diameter, determine the extent of stent migration, and stent shortening after stent placement in the immediate‐, short‐, and long‐term periods, and evaluate inter‐observer reliability of radiographic measurements. Animals: Fifty client‐owned dogs. Methods: Retrospective study in which medical records were reviewed in dogs with CTCS treated with an intraluminal tracheal stent. Data collected included signalment, location, and type of collapse, stent diameter and length, and post‐stent placement radiographic follow‐up times. Radiographs were used to obtain pre‐stent tracheal measurements and post‐stent placement measurements. Results: Immediate mean percentage change was 5.14%, 5.49%, and 21.64% for cervical, thoracic inlet, and intra‐thoracic tracheal diameters, respectively. Ultimate mean follow‐up time was 446 days, with mean percentage change of 2.55%, 15.09%, and 8.65% for cervical, thoracic inlet, and intra‐thoracic tracheal diameters, respectively. Initial mean stent length was 26.72% higher than nominal length and ultimate long‐term tracheal mean stent shortening was only 9.90%. No significant stent migration was identified in the immediate, short‐, or long‐term periods. Good inter‐observer agreement of radiographic measurements was found among observers of variable experience level. Conclusions and Clinical Importance: Use of an intraluminal tracheal stent for CTCS is associated with minimal stent shortening with no clinically relevant stent migration after fluoroscopic placement. Precise stent sizing and placement techniques likely play important roles in avoiding these reported complications.